PERENCANAAN INSTALASI PENGOLAHAN AIR LIMBAH DOMESTIK RUMAH SAKIT MENGGUNAKAN TEKNOLOGI BIOFILTER ANAEROB – AEROB - Rokiin, Moh; -, Nurhayati (Fakultas Teknik - Universitas Satya Negara Indonesia, 2024)
An increase in the number of facilities that serve public health can increase the potential for environmental wastewater pollution, there by impacting human health problems and environmental pollution. The aim of the research is to determine the planning of the RSU X domestic wastewater treatment plant using anaerobic-aerobic biofilter technology. The research method uses a qualitative descriptive approach. The research population was all RSU X liquid waste, the sampling technique used non-probability sampling in the form of saturated sampling, while the research sample was domestic liquid waste at RSU X. The research results show that the Waste Water Treatment Plant (IPAL) planning is designed to treat waste water of ± 30 m3 / day, with a capacity of 60 beds. The removal efficiency of waste water characteristics in the inlet chamber tank, grease trap tank, equalizing tank, anaerobic biofilter tank, aerobic biofilter tank, sedimentation tank and chlorination tank. Efficiency of chlorine requirements for disinfection, CH4 generation efficiency, and sludge generation efficiency.